New sites expanding the "Sardinian cold‐water coral province" extension: A new potential cold‐water coral network?. Issue 1 (20th November 2018) - Moccia, Davide; Cau, Alessandro; Alvito, Andrea; Canese, Simonepietro; Cannas, Rita; Bo, Marzia; Angiolillo, Michela; Follesa, Maria Cristina
Abstract: Cold‐water coral (CWC) ecosystems are protected both in national and international waters. They are considered Vulnerable Marine Ecosystems and, in addition, meet the criteria to be defined ecological or biological significant areas. Two new sites of the "Sardinian CWC province" were discovered by means of remotely operated vehicle surveys in two submarine canyons in the north‐eastern portion of the Sardinian continental margin, at depths ranging from 230 to 430 m. Dense and healthy patches of small and medium‐sized Madrepora oculata colonies were found dwelling on rocky walls and inclined silted soft bottoms. A rich and diverse associated megafauna was found within both live and dead portions of the coral framework. In addition, the presence of benthic litter and derelict fishing gears were also documented. These results further extend the "Sardinian CWC province" extension, providing insights of a potential CWC network along the Sardinian continental margin with implications for the Mediterranean mosaic of CWC provinces, further stressing the need for urgent conservation measures for these habitats.